2020
DOI: 10.3390/toxins12050284
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of Potential Harmful Cyanobacteria and Cyanotoxins in the Obrzyca River (Poland), a Source of Drinking Water

Abstract: Harmful cyanobacteria and their cyanotoxins may contaminate drinking water resources and their effective control remains challenging. The present study reports on cyanobacterial blooms and associated cyanotoxins in the Obrzyca River, a source of drinking water in Poland. The river was examined from July to October 2019 and concentrations of microcystins, anatoxin-a, and cylindrospermopsin were monitored. The toxicity of water samples was also tested using an ecotoxicological assay. All studied cyanotoxins were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…CYN, a toxic metabolite from cyanobacteria, has come to light in recent years because of its global occurrence, bioaccumulation, and multi-organ toxicity. CYN is extraordinarily soluble in water and is not only biologically refractory , but chemically stable under natural environmental conditions. , Accordingly, CYN as a serious contaminant prevails in waters from subtropical areas and inland waters, even in drinking water reservoirs and rivers. ,, Especially, the occurrence of CYN in drinking water sources makes its removal a great challenge for drinking water plants . Our previous study showed that BiOBr could oxidize CYN under visible-light irradiation but its h Br 4p + was not high enough to oxidize H 2 O, generating • OH radicals, and only 12.9% of CYN was adsorbed on the BiOBr surface at adsorption equilibrium .…”
Section: Introductionmentioning
confidence: 99%
“…CYN, a toxic metabolite from cyanobacteria, has come to light in recent years because of its global occurrence, bioaccumulation, and multi-organ toxicity. CYN is extraordinarily soluble in water and is not only biologically refractory , but chemically stable under natural environmental conditions. , Accordingly, CYN as a serious contaminant prevails in waters from subtropical areas and inland waters, even in drinking water reservoirs and rivers. ,, Especially, the occurrence of CYN in drinking water sources makes its removal a great challenge for drinking water plants . Our previous study showed that BiOBr could oxidize CYN under visible-light irradiation but its h Br 4p + was not high enough to oxidize H 2 O, generating • OH radicals, and only 12.9% of CYN was adsorbed on the BiOBr surface at adsorption equilibrium .…”
Section: Introductionmentioning
confidence: 99%
“…However, different geographical origins, species and environmental factors might influence which congeners are more abundant. Analysis of the most common congeners during monitoring is therefore still advisable [20,[53][54][55]71,76,77,85,86].…”
Section: Discussionmentioning
confidence: 99%
“…Cyanobacteria, also known as blue-green algae, occur spontaneously in freshwater [2]. There have been several reports on the toxicity of cyanobacterial bloom in surface waters worldwide [3], [4], [5],[6], [7],[8], [9], [10]. These microbes use the energy of sunlight and x inert atmospheric nitrogen into usable nitrates that can be absorbed by plants [11].…”
Section: Introductionmentioning
confidence: 99%